Investigation of Some mechanical properties of Slurry Infiltrated Fibrous Concrete (SIFCON) Under Different Curing Times - Mahmood, Rand Khaldoon; Khadim, Mohmmed Juaad; Jabbar, Fayq Hassan (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This paper attempts to study the mechanical performance and durability of slurry infiltrated fibrous concrete (SIFCON) made using a liquid infiltration method with carbon and Basalt fibers in different curing environments. The high-performance cementitious composite through the innovative process, in which attached fibers are pre-positioned in the mold and subsequently infiltrated with liquid mixture, possesses special properties that enable its much stronger flexibility and durability as against standard concrete. Ordinary Portland cement (Type I), fine sand, fly ash (30% as replacement of fine aggregate) basalt fibers and carbon were used in the study with high-range water-reducing admixture. Workability was determined by means of tests of slump and flow, whereas the compressive, flexural and splitting strengths at 7, 28 and 56 days were tested. Results showed that basalt fibers enhanced the early-age strength, but their effect was limited in the long term. Carbon fibers significantly improved compressive and splitting strengths, with optimal performance at 3-5% fiber content. Blends containing a combination of carbon and basalt fibers exhibited synergistic effects, achieving compressive strength 69% higher than conventional concrete and splitting strength nearly five times higher. Fly ash addition improved matrix density and bond strength, particularly with increasing age. In general, the results confirm the importance of the type and percentage of fibers, as well as the curing time, in the performance of SIFCON concrete. Using a combination of different types of fibers and extending the curing time provides the best balance between strength, flexibility, and durability.